If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -19 = 9x + 9 Reorder the terms: -19 + 12x = 9x + 9 Reorder the terms: -19 + 12x = 9 + 9x Solving -19 + 12x = 9 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -19 + 12x + -9x = 9 + 9x + -9x Combine like terms: 12x + -9x = 3x -19 + 3x = 9 + 9x + -9x Combine like terms: 9x + -9x = 0 -19 + 3x = 9 + 0 -19 + 3x = 9 Add '19' to each side of the equation. -19 + 19 + 3x = 9 + 19 Combine like terms: -19 + 19 = 0 0 + 3x = 9 + 19 3x = 9 + 19 Combine like terms: 9 + 19 = 28 3x = 28 Divide each side by '3'. x = 9.333333333 Simplifying x = 9.333333333
| 6*77= | | 9x+1=73 | | -49*6= | | 7*16= | | x+.05x=10.23 | | Y^4-361=0 | | 6x+6-340+295x=30 | | X^2-5x+22= | | Y^4-360=0 | | 10*27= | | y^2+8y-33= | | 10=-.66(4x+5) | | 6*52= | | 11x+2=8x+15 | | 3x+9=14-3x | | 2x+7=15-3x | | (5u-6)(1-u)=0 | | 3(35)= | | -3y+5y=-20 | | x+=3 | | 9X+2x^2=18 | | 3x^2-8=10x | | 12x+17=4x+201 | | 4x^2-29x+29=-5x+2 | | 20x+14y=-42 | | -5y+2y=4 | | 289-5x=40x+24 | | 47x+2y=5 | | 4x+81= | | 10x-8=62 | | .83y-.167=3.67 | | 4x-2*(x-3)=17+x |